Ultrasound-assisted Extraction as a Potential Method to Enhanced Extraction of Bioactive Compound - Yushinta Aristina Sanjaya; Pardi Sampe Tola; Rahmawati Rahmawati (Nusantara Science and Technology Proceedings, 2022)
Ultrasound-assisted Extraction (UAE) is one of the potential ways to increase the yield and quality of bioactive compounds. Besides, the UAE is environmentally friendly since the solvent used is a lesser, non-toxic solvent, time-saving, and operated at a lower temperature, leading to the increase of mass transfer. Ultrasound is one of the wave sounds that have a frequency range that is above the range that can be heard by humans (20 MHz). This wave could cause the breakdown in plant tissue via cavitation, the forming of vacuum bubbles from a wave sound on a liquid material. The breakdown of plant tissue leads to the release of bioactive compounds. These compounds, then, are dissolved in the solvent. The types of bioactive compounds that can be extracted using ultrasound waves are polyphenols, carotenoids, aromatic compounds, and polysaccharides from plant matrix. The UAE method is affected by the temperature, frequency, and amplitude of the wave, density, types of solvent, extraction time, and plant matrix. This article would review the principles of UAE method, cavitation, the characteristic of tissue exposed to ultrasound, and the devices used during the extraction.